INFLUENCE OF ELECTRONIC MEDIA ON CHILDREN'S PERSONALITY DEVELOPMENT - Menhas, Rashid (Innovare Journal of Social Sciences, 2014)
In the present age world is becoming global village due to modern information and communication systems. The exchange of thoughts and feelings via the spoken or written word is of course, a strong force for group cohesiveness. In complex societies, the electronic media are strategic devices for maintaining (or changing) group identities and loyalties. Electronic media have pervasive influences and are powerful agents of personality development. Personality is conceptualized as a set of stable Knowledge, structures that individuals use to interpret event in their social world and to guide their behavior". The study was conducted in district Gujranwala in Pakistan to investigate the respondent's perception regarding the impact of electronic media on children personality. Through multistage sampling technique, 120 respondents were selected. A structured interview schedule was used for the data collection. After collection of the data, appropriate statistical techniques were applied to draw conclusion. The results show that majority of the respondents agreed that electronic media play a vital role in the development of children's personality, attitudes and behaviour. However, due to the danger of access of children to vulgar, sex obsessed and violent movies, majority of respondents were in favour of negative impact of electronic media on the attitude of their children.